The Widowhood Effect: Explaining the Adverse Outcomes After Spousal Loss Using Physiological Stress Theories, Marital Quality, and Attachment. (July 2020) - Ennis, Jeffrey; Majid, Umair
The loss of a loved one is one of the most ubiquitous life experiences. There have been multiple reviews that have found adverse health outcomes for individuals experiencing spousal loss, particularly the widowhood effect that characterizes an increased risk of mortality after loss. However, there is a lack of clarity on the relationship between physiological stress and the widowhood effect. This commentary uses the literature on stress, marital quality, and attachment to explain the widowhood effect and other adverse physical health outcomes. We discuss three points: (1) the chronic nature of stress may be the source of adverse outcomes, (2) the quality and quantity of available resources may moderate the effects of stress, and (3) the level and style of attachment may explain why these outcomes may persist many years after spousal loss.